IMPLEMENTATION OF THE STORY METHOD BASED ON AUDIOVISUAL MEDIA TO IMPROVE LIVING ABILITY AND THINKING SYMBOLIC ABILITY OF CHILDREN (Classroom Action Research study in the year-old Trustee Kindergarten) - Martuti Martuti; Bayu Insanistyo (UNIB Press, 2018)
The purpose of this study is to describe the application of Audio Visual media- based storytelling methods in improving listening skills and the ability to symbolic thinking of early childhood at the State Trustees of the North Bengkulu Regency. The research method used is collaborative CAR means that researchers or teachers together do learning to improve quality or learning outcomes. The subjects of this study were children in group B of the National Trustees of the Kindergarten of North Bengkulu Regency, totaling 15 people. Data collection techniques using observation sheet data analysis using percentages and t-test. Therefore the use of effective storytelling methods to improve listening skills and early childhood symbolic thinking skills with theresults of the study shows that Audio Visual media-based storytelling methods can significantly improve listening skills and the ability to symbolize early childhood at the National Trustees of Ketahun North Bengkulu Regency.